2012
DOI: 10.3354/esr00400
|View full text |Cite
|
Sign up to set email alerts
|

Changes in range-wide distribution of plains topminnow Fundulus sciadicus

Abstract: Globally, riverine fishes are affected by degradation of habitat, stream alterations, lost stream connectivity and introduction of non-native species. The plains topminnow Fundulus sciadicus, a small stream-dwelling fish, currently does not have a federal conservation status in the USA; however, anecdotal reports have suggested its decline for the last 20 yr. Our goals were to evaluate the validity of its reported decline and to determine the current range-wide status of this species. We identified 927 histori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Impoundments often support non-native species that compete with native species. For example, plains topminnow distribution has been suggested to be negatively influenced by the presence of non-native species such as largemouth bass (Micropterus salmoides) and mosquitofish (Gambusia affinis) (Fischer & Paukert, 2008a;Pasbrig et al, 2012). Impoundments have also been associated with reduced habitat and populations of suckermouth minnow, slenderhead darter, and bigmouth shiner (Quist et al, 2005;Heimann et al, 2007).…”
Section: Model Development and Evaluationmentioning
confidence: 97%
“…Impoundments often support non-native species that compete with native species. For example, plains topminnow distribution has been suggested to be negatively influenced by the presence of non-native species such as largemouth bass (Micropterus salmoides) and mosquitofish (Gambusia affinis) (Fischer & Paukert, 2008a;Pasbrig et al, 2012). Impoundments have also been associated with reduced habitat and populations of suckermouth minnow, slenderhead darter, and bigmouth shiner (Quist et al, 2005;Heimann et al, 2007).…”
Section: Model Development and Evaluationmentioning
confidence: 97%
“…Prior to reintroduction efforts, we sampled the local fish assemblage using 3-pass depletion backpack electrofishing with block-nets. This assessment, paired with recent range-wide sampling efforts (see Pasbrig et al 2012), confirmed that plains topminnow were not present at reintroduction sites.…”
Section: Study Areamentioning
confidence: 74%
“…Plains topminnow is a habitat specialist that occurs in widely distributed, isolated, and dynamic habitat patches characterized by shallow, stagnant water that are especially vulnerable to desiccation by means of prevalent agricultural activities that divert water from the channel or lower the water table (Rahel & Thel 2004;Fischer & Paukert 2008;Pasbrig et al 2012). The isolated nature of plains topminnow populations suggests that stream connectivity may be important to their longterm persistence (Cross & Collins 1995;Pflieger 1997;Rahel & Thel 2004;Pasbrig et al 2012).…”
mentioning
confidence: 97%
“…Plains topminnow, Fundulus sciadicus, populations have declined in both distribution and local abundance throughout their native range (Rahel & Thel 2004;Pasbrig et al 2012). Declining water quality and quantity, habitat degradation, population fragmentation, and the introduction of nonnative fishes have resulted in declines of other Great Plains stream fishes (Haslouer et al 2005), and likely influence the persistence of this species (Rahel & Thel 2004;Pasbrig et al 2012).…”
mentioning
confidence: 98%
See 1 more Smart Citation